Challenging assumptions: the gendered nature of mosquito net fishing and the implications for management. (2nd January 2020) - Short, Rebecca E.; Mussa, Jamen; Hill, Nicholas A. O.; Rowcliffe, Marcus; Milner-Gulland, E. J.
Abstract: Mosquito net fishing (MNF) is a growing activity globally, particularly in places where mass distributions of nets are a public health policy to tackle malaria. Due to the mesh sizes used, and therefore its assumed 'indiscriminate' nature, MNF is thought to be unsustainable and a threat to both fisheries resources and biodiversity. As a consequence, MNF is widely illegal. While a body of evidence is growing as to the scale of MNF, few detailed case studies exist and none explicitly address the assumptions of ecological harm. Here, we present a first full characterization and gear comparison for MNF within the small-scale fisheries of Cabo Delgado, Northern Mozambique. The assumptions of harm to the fishery are challenged by the characterization of MNF as highly gendered in this case; with a primarily androcentric deployment method posing some risk to the fishery but a predominantly gynocentric method demonstrating possibility of limited resource overlap with other gears and little evidence of ecosystem-level impacts. The gendered nature of the fishery is discussed in terms of both risks and benefits to the fishery, with a critical need for further socio-economic assessment identified in order to guide more effective and equitable management of MNF.